2019
DOI: 10.5935/0004-2749.20190027
|View full text |Cite
|
Sign up to set email alerts
|

O olho na hepatite C: uma revisão

Abstract: | This review aims to caution ophthalmologists about the ocular consequences leading to the diagnosis of hepatitis C virus infection. In addition, in this context, the effects of old and new drugs are discussed in the ophthalmological setting. The importance of early diagnosis and the curative treatment of the disease has been reported in the national and international literature, demonstrating that its progression has important implications for daily clinical and surgical ophthalmological practice. Despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The specific mechanism through which chronic HCV infection causes AMD remains unclear. The pathogenesis of ocular changes may be the direct action of viral and immunological reactions to certain viral antigens and even immune complexes [ 27 ]. On the basis of the findings of their in vitro experiments, Pazienza [ 35 ] reported that HCV itself possesses regulatory genes that can cause ocular pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific mechanism through which chronic HCV infection causes AMD remains unclear. The pathogenesis of ocular changes may be the direct action of viral and immunological reactions to certain viral antigens and even immune complexes [ 27 ]. On the basis of the findings of their in vitro experiments, Pazienza [ 35 ] reported that HCV itself possesses regulatory genes that can cause ocular pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dry eye disease [ 25 ] and ischemic retinopathy caused by either HCV-induced vasculitis [ 20 ] or interferon treatment [ 25 , 26 ] have been reported to be strongly associated with the ocular manifestations of HCV infection. The pathogenesis of ocular changes may be the direct action of viral and immunological reactions to certain viral antigens and even immune complexes [ 27 ]. However, evidence suggesting an association of between HCV infection and AMD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…22 The occurrence of cirrhosis and other associated complications can be mitigated if the physician detects the initial HCV infection symptoms and makes use of the available therapy. 23…”
Section: Introductionmentioning
confidence: 99%